Copy Number Variation of Transposable Elements in Thinopyrum intermedium and Its Diploid Relative Species - Divashuk, Mikhail G. (Plants (Basel), 2019)
Diploid and polyploid wild species of Triticeae have complex relationships, and the understanding of their evolution and speciation could help to increase the usability of them in wheat breeding as a source of genetic diversity. The diploid species Pseudoroegneria spicata (St), Thinopyrum bessarabicum (J(b)), Dasypyrum villosum (V) derived from a hypothetical common ancestor are considered to be possible subgenome donors in hexaploid species Th. intermedium (J(r)J(vs)St, where indices r, v, and s stand for the partial relation to the genomes of Secale, Dasypyrum, and Pseudoroegneria, respectively). We quantified 10 families of transposable elements (TEs) in P. spicata, Th. bessarabicum, D. villosum (per one genome), and Th. intermedium (per one average subgenome) using the quantitative real time PCR assay and compared their abundance within the studied genomes as well as between them. Sabrina was the most abundant among all studied elements in P. spicata, D. villosum, and Th. intermedium, and among Ty3/Gypsy elements in all studied species. Among Ty1/Copia elements, Angela-A and WIS-A showed the highest and close abundance with the exception of D. villosum, and comprised the majority of all studied elements in Th. bessarabicum. Sabrina, BAGY2, and Angela-A showed similar abundance among diploids and in Th. intermedium hexaploid; Latidu and Barbara demonstrated sharp differences between diploid genomes. The relationships between genomes of Triticeae species based on the studied TE abundance and the role of TEs in speciation and polyploidization in the light of the current phylogenetic models is discussed.